ANALISIS TINGKAT KEPERCAYAAN PUBLIK TERHADAP MAHKAMAH KONSTITUSI PASCA PUTUSAN NOMOR 90/PUU-XXI/2023 - Yuliana, Adelia; Tuasalamony, Adzra Ardelia; Al Fath; Parhusip, Alizcia Dora; Febriani, Anggie; Bakhtiar, Handar Subhandi (Jurnal Hukum Statuta, 2024)
Constitutional Court Decision Number 90/PUU-XXI/2023 is considered to have a conflict of interest due to the involvement of Chief Justice Anwar Usman's family with one of the parties, raising doubts about the court's independence and integrity. This study aims to examine the impact of this decision on public perception and trust in the Constitutional Court. Using empirical legal research with an interdisciplinary and conflict approach, the study distributed online questionnaires through Google Forms to explore the impact of that Decision on public perception and trust. The results indicate that the decision to set the minimum age limit for presidential and vice-presidential candidates at 40 years old has a significant impact on the level of public trust in the Constitutional Court. The Spearman correlation test shows a very strong and significant relationship, with a coefficient of determination of 0.780, indicating that 78% of the variability in the level of public trust can be explained by this decision. However, there is still 22% variability influenced by other factors that need to be studied further to get a more complete picture of public trust in the Constitutional Court.